Bridging the Urban-Rural Divide: Leveraging Technology for Development and Connectivity in Small Village, Indonesia - Savandha, Septien Dwi (Politeknik Siber Cerdika Internasional, 2024)
Indonesia's rural areas face significant digital disparities that hinder socio-economic development and limit residents' access to essential services. This study investigates the impact of digital inclusion on small Indonesian villages, examining how improved connectivity can foster economic growth, educational access, and healthcare availability. The research employs a qualitative approach, utilizing semi-structured interviews and thematic analysis to capture perspectives from village residents, local leaders, and organizations involved in digital initiatives. Findings reveal that internet access positively affects income potential, as residents can expand their businesses and access digital resources. Furthermore, digital literacy programs tailored for different age groups are critical in encouraging adoption across generations and addressing age-related technology gaps. The study emphasizes the necessity of government-private partnerships to expand rural infrastructure sustainably. Practical implications suggest that inclusive digital policies and adaptive infrastructure strategies are fundamental to bridging the urban-rural divide. This research provides a strategic framework for future digital inclusion efforts, supporting Indonesia’s vision of a digitally connected society.